2016
DOI: 10.1080/20786190.2016.1254929
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver satisfaction with a multidisciplinary community-based rehabilitation programme for children with cerebral palsy in South Africa

Abstract: This study sought to determine the levels of satisfaction and experiences of caregivers with a multidisciplinary rehabilitation programme. A total of 26 caregivers were recruited at 3 health settings in South Africa. A survey based on the Multidimensional Assessment of Parental Satisfaction for Children with Special Needs and focus-group discussions were conducted at the end of programme. The majority of the respondents were mothers and unemployed. The participants were generally satisfied with the rehabilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…The results were comparable with a previous study which identified parents as the primary persons to take care of disabled child followed by grandmother and sibling (Dambi & Jelsma, 2014). The findings in our study were also similar to studies conducted in the African subcontinent, which found that the majority of caregivers were mothers, while men played the role as income providers (Khamis & Njau, ;Ngubane & Chetty, 2017). The ethnic group analysis for the parents with disabled children in this study found that most of them was Malay; this result may be influenced by the study location which was conducted in suburban area with most of the population being in the Malay ethnic group.…”
Section: Demographic Characteristicssupporting
confidence: 91%
See 2 more Smart Citations
“…The results were comparable with a previous study which identified parents as the primary persons to take care of disabled child followed by grandmother and sibling (Dambi & Jelsma, 2014). The findings in our study were also similar to studies conducted in the African subcontinent, which found that the majority of caregivers were mothers, while men played the role as income providers (Khamis & Njau, ;Ngubane & Chetty, 2017). The ethnic group analysis for the parents with disabled children in this study found that most of them was Malay; this result may be influenced by the study location which was conducted in suburban area with most of the population being in the Malay ethnic group.…”
Section: Demographic Characteristicssupporting
confidence: 91%
“…Satisfaction level of patients, parents or/and caregivers would help to provides information and knowledge about the practice and marketability of health services (Ngubane & Chetty, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Although the literature is limited regarding adolescent mothers’ satisfaction with the multidisciplinary approach of care, several studies within the healthcare context report that patients who received care from an MDT were satisfied with the care. 35,36…”
Section: Discussionmentioning
confidence: 99%
“…16 A previous study conducted in Zimbabwe also found improvement in social support, environmental limitation, and outcomes of a rehabilitation program by creating a specific appointment for rehabilitation sessions. 17 This shows that a systematic rehabilitation program has a high impact on the disabled child as well as to the parents and caregivers. Thus, adequate training by the CBR workers should be given attention.…”
Section: Discussionmentioning
confidence: 99%